Hepatic Failure and Hepatorenal Syndrome Secondary to Erlotinib: A Possible Etiology of Complications in a Patient with Pancreatic Cancer - Gunturu, Krishna S; Abu-Khalaf, Maysa; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Yale New Haven Hospital. New Haven, CT, USA.